Elastography acoustic radiation force impulse (ARFI): An investigation of ocular elasticity in dogs with chronic secondary glaucoma - Madruga, Gabriela Morais [UNESP] (2021)
The aim of this study was to evaluate and compare the elasticity of the optic nerve (ON) and retinal-choroid-sclera complex (RCSC) in dogs with healthy eyes and secondary glaucoma using ARFI elastography. ARFI elastography was performed on normal eyes (n = 25) and affected by glaucoma (n = 25). The mean values of shear wave velocity (SWV) of the ON and RCSC were compared between groups by the Student’s t-test. The correlation between elastography measurements of the ON and RCSC and the intraocular pressure (IOP) was measured. The SWV of the optic nerve in glaucomatous eyes (4.77 ± 1.59 m/s) was being significantly higher than in healthy eyes (2.34 ± 0.45 m/s) (p < 0.0001). RCSC shear wave velocity values in glaucomatous and healthy eye were 4.26 ± 1.28 m/s and 2.36 ± 0.40 m/s, respectively, demonstrating increased stiffness in the glaucomatous group (p < 0.0001). RCSC and ON shear wave velocity did not correlate with size of the vitreous chamber and ON as measured by B-mode ultrasound (p > 0.05). However, there was a slight positive correlation between RCSC and ON shear velocity in the glaucoma group (r = 0.38; p = 0.05). The shear wave velocity rate values of ON and RCSC tissues in glaucomatous eyes are greater than in healthy eyes, suggesting that they are less elastic, or harder, in glaucomatous eyes.